VOC dan Dampaknya Terhadap Indonesia - Tarmizy Idris (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2012)
Before the European invaded Indonesia, the capitalistic trade system in Indonesia had grown up. But such kind of system strongly related to political issues which caused the birth of bureaucratic capitalism. The situation didn't enable the free capitalistic trade system to grow up rapidly. The arrival of VOC had made seious change in Indonesia capitalistic system that time. The predominance of VOC's bureaucracy and military had blessed it the power to uphold monopoly system in Indonesia trade and destroy its capitalistic system. Basically, the downfall of Indonesian capitalistic system was caused by its weak cultural system which didn't have a strong foundation for capitalism. The Indonesian cultural values didn't protect the property right of people. Moreover, the absolute power of Kings didn't give conducive opportunities to the people to accumulate their capital and develop thier business. ———– AbstrakSebelum kedatangan bangsa-bangsa Eropa ke Nusantara. Di Indonesia telah berkembang perdagangan dengan kapitalisme yang kuat. Tetapi perdagangan itu selalu terkait erat dengan permasalahan politik, sehingga memunculkan kapitalisme birokrat. Situasi ini tidak memungkinkan berkembangnya kapitalisme yang memiliki etos perdagangan bebas. Kedatangan VOC telah membawa dampak sangat serius terhadap kapitalisme Indonesia. Keunggulan VOC dalam bidang birokrasi dan militer memberikan kekuatan kepadanya untuk menegakkan sistem monopoli dalam perdagangan di Indonesia, yang menghancurkan kapitalisme Indonesia. Kehancuran kapitalisme Indonesia pada dasarnya lebih disebabkan sebagai akibat kerapuhan sistem budaya Indonesia yang tidak memberikan pijakan kuat terhadap perkembangan kapitalisme. Nilai-nilai budaya Indonesia tidak memiliki perlindungan yang kuat terhadap hak milik pribadi rakyat. Disamping itu, kekuasaan absolut para raja dengan tindakannya yang sewenang-wenang tidak memberikan peluang kondusif untuk perkembangan perdagangan dan akumulasi modal pada rakyat.